Lexical cohesion and the repetition matrix - Sardinha, Antonio Paulo Berber (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The study of lexical cohesion has been commonly done in relation to the issue of texture. However, lexical cohesion is also capable of revealing another textual property: the segmentability, that is, as a text is formed of several interconnected parts simultaneously. One lexical cohesion research technique that can be reused for segmentation investigation is 'bonding analysis'. In this type of analysis are described the various cohesive bonds that are formed throughout the text, with the possibility of manipulation of the degree of adhesion. In addition, the results of the adhesion analysis are shown in a numerical matrix, which makes it possible to visualize the distribution of the cohesive loops of the text. In this work, these properties of the adhesion analysis are channeled into the segmentation analysis through a procedure called 'vicinity strip'. The procedure is described, applied, and the results are discussed.